(3QSGdJGf aj CUhd GdJaSjQ (B:s (3eHMK aj GdESQGFjdjGJ hCeKdI dgG aj ShQJj (B((3U(B-(3hGdUGaGJ(B) : (3eOQSI GdJaSjQ HGdYQGb aj YgO GdJGHYjf (B/s - (3GdYjfGJj, LGSe Hf eMeOs ((3GdchjJ (B:s (3ecJHI GdEeGe GdPgHj ddfTQ hGdJhRjY,s, 2010)
(3CUhd GdJaSjQ, GdESQGFjdjGJ(B.s
Keywords: (3GdbQBfs -- (3JaSjQs -- (3GdYQGbs; (3GdbQBf(B.s -- (3JaGSjQs; (3GdbQBf(B.s -- (3JaGSjQs; (3GdESQGFjdjGJs